2016
DOI: 10.1093/toxsci/kfw170
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Catalytic Antioxidant Rescue of Inhaled Sulfur Mustard Toxicity

Abstract: Sulfur mustard (bis 2-chloroethyl ethyl sulfide, SM) is a powerful bi-functional vesicating chemical warfare agent. SM tissue injury is partially mediated by the overproduction of reactive oxygen species resulting in oxidative stress. We hypothesized that using a catalytic antioxidant (AEOL 10150) to alleviate oxidative stress and secondary inflammation following exposure to SM would attenuate the toxic effects of SM inhalation. Adult male rats were intubated and exposed to SM (1.4 mg/kg), a dose that produces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The utility of Mn III TDE-2-ImP 5+ extends beyond OP exposures with the ability to limit toxicity resulting from other chemical agents in post-exposure treatment paradigms. Mn III TDE-2-ImP 5+ has been demonstrated to improve mortality and inhibit lung, skin and nasal damage resulting from exposure to the vesicating and alkylating agent, sulfur mustard and its analog, 2-chloroethyl ethyl sulfide (CEES) ( McElroy et al, 2016 ; O’Neill et al, 2011 ; O’Neill et al, 2010 ; Tewari-Singh et al, 2014 ). The compound was also found to protect the lung from exposure to chlorine gas ( McGovern et al, 2011 ).…”
Section: Antioxidant Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of Mn III TDE-2-ImP 5+ extends beyond OP exposures with the ability to limit toxicity resulting from other chemical agents in post-exposure treatment paradigms. Mn III TDE-2-ImP 5+ has been demonstrated to improve mortality and inhibit lung, skin and nasal damage resulting from exposure to the vesicating and alkylating agent, sulfur mustard and its analog, 2-chloroethyl ethyl sulfide (CEES) ( McElroy et al, 2016 ; O’Neill et al, 2011 ; O’Neill et al, 2010 ; Tewari-Singh et al, 2014 ). The compound was also found to protect the lung from exposure to chlorine gas ( McGovern et al, 2011 ).…”
Section: Antioxidant Strategiesmentioning
confidence: 99%
“…It may be used at the site, ambulance or in the hospital setting as it targets late effects; however, earlier intervention with daily injectable dosing would be optimal. In animals, Mn III TDE-2-ImP 5+ was effective at protecting the lung and skin when given at 5 mg/kg up to one hour after exposure to sulfur mustard or CEES ( McElroy et al, 2016 ; O’Neill et al, 2011 ; O’Neill et al, 2010 ; Tewari-Singh et al, 2014 ). Doses ranging from 5 to 7 mg/kg were sufficient to protect the brain from nerve agents and their surrogates when given 15 min to one hour following exposure ( Liang et al, 2018a ; Liang et al, 2018b ; Pearson et al, 2015 ).…”
Section: Antioxidant Strategiesmentioning
confidence: 99%
“…Direct administration of tissue plasminogen factor into airways can eliminate or reverse airways obstruction by fibrin, and prevent gas exchange abnormalities and respiratory failure (135,136). These therapies for the acute process might be complemented by catalytic antioxidants (141), flavonones (142), and/or cell-based therapies (143).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Moreover, during the recent decades, it was applied against some nations such as Iran and Syria, too. [1][2][3] Cellular and molecular biology-based studies have indicated that SM can alkylate DNA and proteins, destroy enzymes, induce free radicals, and finally can cause necrosis and apoptosis in cells. In addition to death and acute complications, SM can cause long-term side effects on the lungs, skin, and eyes of its victims.…”
Section: Introductionmentioning
confidence: 99%